Pediatric Knee Arthroscopy: The Basics of Pediatric Knee Arthroscopy from a Collection of Pediatric Sports Medicine Experts - Julia Kirby MBBS, MSpMed; Benjamin Johnson MPAS, PA-C; Matt Millewski MD; Kevin Shea MD; Jennifer Beck MD; Philip L. Wilson MD; Matthew Schmitz MD; Todd Milbrandt MD; Eric Edmonds MD; Lee Pace MD; Curt Vandenberg; Marc Tompkins MD; et al. (SAGE Publishing, 2023)
Background/Objective: To share technical pearls of a basic knee arthroscopy in a pediatric patient by presenting tips and tricks used by experienced pediatric arthroscopists. Indications: Knee arthroscopy is a common procedure performed by most orthopedic surgeons. However, technical considerations and equipment should be considered before performing this procedure in a pediatric patient. This video provides information on indications, equipment, and patient positioning, as well as outlining a systematic approach to diagnostic arthroscopy and pertinent pediatric anatomy. Discussion/Conclusion: This video provides an excellent overview as well as specific pathology-dependent considerations for the inexperienced orthopedic surgeon, or the orthopedic surgeon who rarely performs knee arthroscopy. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.